2007
DOI: 10.1097/md.0b013e3181568ec0
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of Methotrexate for Cyclophosphamide in Wegener Granulomatosis

Abstract: We conducted a retrospective review to assess outcomes of therapy in patients with newly diagnosed Wegener granulomatosis (WG) using methotrexate (MTX) for mild to moderate disease and short-term treatment with cyclophosphamide (CYC) followed by MTX for severe disease. Patients with WG were included if their initial plan of therapy and subsequent care were directly supervised by the Cleveland Clinic Center for Vasculitis Care and Research. Severe disease (immediately life-threatening or involving critical orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 15 publications
3
41
0
2
Order By: Relevance
“…In the context of AAV, our data-on a cohort level-are in-line with the plausible notion stemming from a relatively large study stating that lymphocyte counts inversely associate with sustained remission [7]. However, by combining cohort-derived data and analyses in individual patients, our results indicate that the value of individual lymphocyte counts in reXecting treatment-eYciency is limited.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the context of AAV, our data-on a cohort level-are in-line with the plausible notion stemming from a relatively large study stating that lymphocyte counts inversely associate with sustained remission [7]. However, by combining cohort-derived data and analyses in individual patients, our results indicate that the value of individual lymphocyte counts in reXecting treatment-eYciency is limited.…”
Section: Discussionsupporting
confidence: 70%
“…How circulating lymphocyte counts relate to disease activity, however, remains controversial. One study reported that treatment-induced lymphopenia (·0.5 £ 10 9 /L) is associated with a high likelihood to achieve sustained remission [3,7]. By contrast, another group suggested that, analogous to patients with systemic lupus erythematodes, lymphopenia in AAV reXects disease activity, with lymphocyte counts actually increasing in patients achieving remission [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…These have included an open-label study of MTX after daily CyP induction in which a 3·7% mortality rate was seen, in which sustained remission occurred in 78% of patients and serious infections in 17% [10]. A randomized trial comparing AZA to MTX for remission maintenance showed that these agents had a comparable rate of toxicity and relapse in eligible patients without contraindications to these agents [11].…”
Section: Induction-maintenance Regimensmentioning
confidence: 99%
“…Both minor and major relapse rates were high in both regimens and associated with increases in CS and CYC therapy and also the use of several others immunosuppressive agents. The high relapse rate observed is also reminiscent of the clinical response to immunosuppressive therapy observed in other vasculitic disorders [6]. CSS is a much rarer vasculitic disorder that may have also played a role in the inability of the investigators to reach the number of patients (n = 110) needed for statistical power.…”
Section: Editor's Commentsmentioning
confidence: 96%